Impacts of anthropogenic source from the nuclear fuel reprocessing plants on global atmospheric iodine-129 cycle: A model analysis. (July 2018) - Kadowaki, Masanao; Katata, Genki; Terada, Hiroaki; Suzuki, Takashi; Hasegawa, Hidenao; Akata, Naofumi; Kakiuchi, Hideki
Abstact: The long-lived radioactive iodine ( 129 I) is a useful geochemical tracer of radioactivity in the atmospheric environment. Although the behavior of 129 I in the atmosphere is still not fully known because of lack of continuous monitoring, we recently observed clear seasonal trends in air concentration and deposition of 129 I in Japan. Using these data, we developed a global atmospheric 129 I transport model to reveal key processes for the global atmospheric 129 I cycle. The physical and chemical processes of advection, turbulent diffusion, dry and wet deposition, atmospheric photolysis, gas–particle conversion in the atmosphere, anthropogenic sources of 129 I discharged from operating nuclear fuel reprocessing plants, and natural sources of 129 I volatilized from ocean and land were included into the model. The model generally reproduced the observed seasonal change in monthly air concentration and deposition of 129 I in Japan, and the global distribution of 129 I concentration in rain as presented in past literature. Numerical experiments changing the intensity of anthropogenic and natural sources were conducted to quantify the impact of anthropogenic sources on the global 129 I cycle. The results indicated that the atmospheric 129 I from the anthropogenic sources was readily deposited in winter and can be accumulated mainly in the northern part of Eurasia. In contrast, the atmospheric 129 I from the natural sources dominated the deposition in summer. These results suggested that the re-emission process of 129 I from the Earth's surface may be important as a secondary impact of 129 I in the global-scaled environment. Furthermore, although wet deposition dominated the total deposition in the Northern hemisphere, dry deposition regionally and seasonally contributed to the total deposition over arctic and northern part of Eurasia in winter, suggesting that the dry deposition may play a key role in the seasonal change of 129 I deposition in the high latitudes of the Northern hemisphere. Highlights: A global atmospheric iodine-129 ( 129 I) transport model was developed. The model reproduced seasonal changes in 129 I concentration and deposition. The source of 129 I for Northeast Asia and North America are estimated. The dispersion, photolysis and rainfall are key processes for 129 I cycle.